The Socio Economic Impacts of the Foreign Workers on the Community of Pengerang, Kota Tinggi - Rahmah Awang, Siti; Norulkamar Ungku Ahmad, Ungku; Zakuan, Norhayati; Jusoh, Ahmad; Sui Hong, Tan (International Journal of Engineering and Technology, 2018)
The RAPID Project that belongs to Petronas and its overflowing activities are able to create thousands of job opportunities. The challenges in meeting the needs of workers have forced the involved contractors who have been hired by Petronas to employ foreign workers due to lack of local workers. The influx of foreign workers indirectly has affected the local community in a negative way. Hence, a specific study on the influx of the foreign workers from various countries and the impact onto the local community was done. The population of this study was divided into two major groups which were 11 organizations representing stakeholders of the project, and nine villages which were affected by the PIPC development; seven were from Taman Bayu Damai and two were from the area of Pengerang, they were Kg. Sungai Rengit and Kg. Punggai. This study was divided into two major phases which were first, the qualitative phase and the second, was the quantitative phase. A survey questionnaire and interview were employed as the instrument of study. Based on the aspects of economy, findings showed that generally, the residents had negative perception on the influx of foreign workers in Pengerang.Â Â